Detection of possible desertified areas using series and trend map of NDVI estimated by AVHRR sensor from NOAA satellites (1982-2019) - Xu, Han (2024)
The present work we report the detection of possible desertification zones through the series and trend map of NDVI and VCI from the AVHRR sensor of the NOAA satellite series for the period from 1982 to 2019. The data used were acquired from the CLASS/NOAA portal, level 1b, have a spatial resolution of 1 km and temporal resolution of 12 hours. Processing algorithms were developed to estimate monthly NDVI and VCI. Seven possible desertification zones were identified by elaborating series and decadal trend maps of the VCI, in which five zones were located in the coastal region, specifically in the limits of agricultural zones, where the zones with the highest negative decadal trend were Piura (-0.29 dec-1), Chiclayo (-0.36 dec-1) and Chicama (-0.27 dec-1) during the period from 1997 to 2006 while, in the jungle region, the highest negative trend was recorded in Huepetuhe, district of Madre de Dios with a value of -0.25 dec-1 in the period from 2007 to 2018. It is proposed that, among the possible desertified areas, the areas in the coastal region (Piura, Chiclayo, Chicama, Pisco and Majes) were generated by intensive agriculture while, the possible desertification of the areas of Pucallpa and Huepetuhe were generated by urban expansion.